Evaluasi Penyaliran di Pit A, sebagai Proyeksi Aktivitas Penambangan PT. Darma Henwa Tbk, Bengalon Coal Project, Kalimantan Timur - Nofi Rahma Maryenti; Murad Murad (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Pit A PT. Darma Henwa Tbk is conducting mine dewatering efforts to remove the water in the pit, to realize the mining plan back in pit A which will be carried out in March 2019. PT. Darma Henwa tbk provided 4 pump units in the mine dewatering activity. However, based on field observations, it is seen that there is still a high level of standing water in sump pit A, this certainly affects the initial mining plan. Therefore, evaluation of the drainage system in pit A. The problem solving method is done by analyzing the design recommendations related to optimizing pump performance and minimizing the fuel available in pit A, namely recommendation I, the design of 2 pump outlets on the highwall and 2 on the sidewall. Recommendation II is to design 1 pump outlet on the highwall and 3 on the sidewall, and recommendation III to design 4 pump outlets on the sidewall. Based on the analysis of the three recommendation, it is concluded that the recommendation I (2 outlet pump in the sidewall and 2 in highwall) solving problems more effectively and efficiently linked system optimization mine dewatering or pumping systems at pit A Bengalon Coal Project, PT. Darma Henwa Tbk.Key Word : Pit A, Mine dewatering, flowrate, pump, fuel